If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(1 + 6x) = 4 + -1x (1 * 4 + 6x * 4) = 4 + -1x (4 + 24x) = 4 + -1x Add '-4' to each side of the equation. 4 + -4 + 24x = 4 + -4 + -1x Combine like terms: 4 + -4 = 0 0 + 24x = 4 + -4 + -1x 24x = 4 + -4 + -1x Combine like terms: 4 + -4 = 0 24x = 0 + -1x 24x = -1x Solving 24x = -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 24x + x = -1x + x Combine like terms: 24x + x = 25x 25x = -1x + x Combine like terms: -1x + x = 0 25x = 0 Divide each side by '25'. x = 0 Simplifying x = 0
| (7x+6)+(5x+3)=(3x-9) | | 3(8)+4=y | | 7x+9=x-21 | | 3x^2-195x-46590=0 | | 5x-4=4+10x | | -24=7+4 | | b-4/9=12/5 | | 10-4x+x=9 | | y+7y=48 | | 12m+20=40 | | 5y+20=5(2-2y) | | a(a-7)+14=2a | | 3x-2+136=180 | | -9+6x=51 | | 0.7m=5.6 | | 10x+10-8x-15=2 | | 5x+10x=50 | | (x-8)(x+7)=-2r | | 5a^2+4a-3=0 | | 2a^3+5a^2-25a=0 | | (3m+13)=31 | | -8p=14 | | 2c-4c=4 | | (3m+13)= | | -6x-9+8x=4 | | 16+4x=(-32) | | x(12-x)=35 | | t/2=2.5 | | 333+5z=-8(9z-6) | | a/4+3= | | m(5m-17)=12 | | .33(x+6)=0.25x+8 |